The role of information systems usage in enhancing port logistics performance: Evidence from the Dar Es Salaam port, Tanzania - James Mlimbila; Ulingeta O. L. Mbamba (Journal of Shipping and Trade (JST), 2018)
This study investigated the role of information systems usage in enhancing port logistics performance using the port of Dar es Salaam, Tanzania, as an example. Specifically, the study examined the role of information systems usage in contributing to reducing shipping and trucking costs, improving on-time delivery of goods and services, increasing trade volume, and enhancing organisational logistics capability. The study employed a quantitative approach, with questionnaires deployed to gather data about information systems usage and the attendant effects. The reliability was measured using Cronbach's alpha. A canonical correlation analysis was performed to estimate the relationship of information systems usage to the port logistics performance. The study established that relationships exist between information systems usage and the perceived decrease in shipping and trucking costs, timely delivery of goods and services, perceived increase in trade volume, and enhanced organisational logistics capability. Based on these findings, the study recommends that ports consider building the capacity of their employees to utilise and manage information systems much more effectively and efficiently to increase the port's performance.
Keywords: 650; Port logistics performance; Information systems usage; Organisational capability